AB0312 Inflammatory activity appears well controlled in most patients with rheumatoid arthritis (RA) in contemporary rheumatology care, but joint damage and distress remain as problems of greater magnitude than inflammation. (12th June 2018) - Pincus, T.; Castrejon, I.; Block, J.A.
Abstract : Background: Rheumatologists traditionally use quantitative measures such as swollen and tender joint counts and laboratory tests to assess inflammatory activity. However, structural damage to joints, as well patient distress seen as fibromyalgia, depression, etc., may be important clinical problems for many RA patients, but are described narratively in the medical record rather than estimated by the physician as quantitative data. Quantitation only of inflammation, while damage and distress are recorded only as narrative descriptions, may limit the capacity to document optimally both clinical status and the rationale for clinical decisions, such as non-intensification of therapy according to "treat-to-target" in patients who may have moderate or high scores on an RA index 1 . We have used 0–10 visual analogue scales (VAS) to score not only physician global assessment (DOCGL), but also levels of inflammation, damage, and distress. Objectives: To analyse 0–10 VAS for DOCGL, as well as for levels of inflammation, damage, and distress in patients with rheumatoid arthritis (RA). Methods: At one academic site, rheumatologists complete four 0–10 VAS for overall physician global assessment (DOCGL), as well as for inflammation or reversible findings (DOCINF), joint and other organ damage or irreversible findings (DOCDAM), and patient distress such as fibromyalgia, depression, etc. (DOCSTR). In a cross-sectional study, mean values of 4 physician VAS were computed in RA patients, and 3 subgroups were compared according to whether scores for inflammation were 2/10 units higher than for damage, similar for inflammation and damage (within 2/10 units), or 2/10 units higher for damage than for inflammation. Mean levels of the 4 VAS in the 3 groups were compared, using analysis of variance (ANOVA). Results: In 50 unselected RA patients, mean 0–10 DOCGL VAS was 4.2, inflammation VAS 2.2, damage VAS 3.5, and distress VAS 2.2 (table 1). Only 9/50 patients had an inflammation VAS more than 2/10 units greater than damage VAS; in these patients, mean VAS for DOCGL=4.6, inflammation=4.9, damage=2.1, and distress=1.1. In 21 patients in whom inflammation=damage, mean VAS for DOCGL=3.9, inflammation=1.8, damage=2.1, and distress=3.2. In 20 patients with damage >inflammation, mean VAS for DOCGL=4.4, inflammation=1.4, damage=5.7, and distress=1.7. Conclusions: Physician VAS scores indicated that a damage VAS was 50% higher than an inflammation VAS in all 50 RA patients (3.5 vs 2.2), and identical (2.1) in the 9 with an inflammation VAS 2 units higher than a damage VAS or 21 with an inflammation VAS within 2 units of a damage VAS. A mean distress VAS was identical to an inflammation VAS (2.2) in the 50 patients. Control of inflammation remains a primary concern for rheumatologists, but has improved considerably in recent years, as damage and distress may have become more prominent in routine patient care. Systematic quantitative VAS assessment of damage and distress, in addition to inflammation, appears of value to document patient status and support clinical decisions. Reference: [1] Tymms K, et al. Arthritis Care Res (Hoboken)2014;66:190–6. Disclosure of Interest: T. Pincus Shareholder of: Dr. Pincus holds a copyright and trademark for MDHAQ and RAPID3 for which he receives royalties and license fees. All revenue is used to support further development of quantitative questionnaire measures for patients and doctors in clinical rheumatology care., I. Castrejon: None declared, J. A. Block: None declared